Exposing the ICT Regulatory Dilemma: The Test for Governments - Njotini, Mzukisi (Obiter, 2020)
Information and Communications Technologies (ICTs) generate both benefits and challenges for society. For example, ICTs augment social development and encourage equality and inclusivity. In addition, these technologies create a new space – that is, cyberspace. This space is separate from physical or offline space. The emergence of this space has resulted in regulators having difficulty establishing suitable regulations. The latter are regulations that understand the workings and dynamics of ICTs. Mostly, regulators adopt regulatory frameworks that are suitable for controlling physical or offline environments. These regulations accept, inter alia, that the source of regulating is the law or legal rules. In the main, regulators continuously re-invent the ICT regulatory wheel in the hope that, by chance, suitable ICT regulations will emerge or be found. Consequently, ICT regulations often exacerbate the existing ICT regulatory dilemma. This article examines an alternative approach to regulations that is external to the law or legal rules. The structure accepts that a proper ICT regulatory framework is one that understands the workings and dynamics of these technologies. Given this understanding, ICT regulations should be bound to the technology and be able to develop or evolve with it.